2019
DOI: 10.1186/s13722-019-0151-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementing alcohol use disorder pharmacotherapy in primary care settings: a qualitative analysis of provider-identified barriers and impact on implementation outcomes

Abstract: Background: Despite the high prevalence of alcohol use disorders (AUDs), in 2016, only 7.8% of individuals meeting diagnostic criteria received any type of AUD treatment. Developing options for treatment within primary care settings is imperative to increase treatment access. As part of a trial to implement AUD pharmacotherapy in primary care settings, this qualitative study analyzed pre-implementation provider interviews using the Consolidated Framework for Implementation Research (CFIR) to identify implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…One study described champions as being important in the initial adoption of an intervention, and as clinician self-efficacy increased, clinician experiences and that of colleagues became more important to sustained use (Green et al, 2014). In addition, the importance of stability in the clinical champion role as determining its effectiveness was also observed (Hagedorn et al, 2019). One study found that a change in the clinical champion in the implementation phase became a barrier to adoption, and immediately affected degree of implementation (Forchuk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One study described champions as being important in the initial adoption of an intervention, and as clinician self-efficacy increased, clinician experiences and that of colleagues became more important to sustained use (Green et al, 2014). In addition, the importance of stability in the clinical champion role as determining its effectiveness was also observed (Hagedorn et al, 2019). One study found that a change in the clinical champion in the implementation phase became a barrier to adoption, and immediately affected degree of implementation (Forchuk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…31 The primary intervention characteristic barrier found in prior research is complexity. 28,29,32 Outer setting characteristics enabling intervention implementation in healthcare settings include the following: relationships between the healthcare organization and other organizations 31 and the presence of best practice examples in other healthcare organizations. 28 No outer setting barriers have been identified in CFIR research in the preparation phase.…”
Section: Introductionmentioning
confidence: 99%
“…28 Inner setting characteristics identified as barriers to interventions were: competing organizational priorities 29,31 and perceived lack of compatibility with existing work routines and technology systems. 32 Characteristics of individuals identified as facilitators in healthcare settings include the following: knowledge and beliefs about the intervention, 28 self-efficacy 29 and a sense of belonging among the staff. 31 Individual characteristic barriers include the following: resistance to new routines, 28 limited knowledge or negative attitudes about the intervention, 30,32,33 and turnover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14) Finally, the fth domain focuses on the implementation process, such as the role of engagement and evaluation. (14) CFIR has been applied to the eld of smoking cessation (17,18) and substance use disorders, (19,20) but has not been utilized to understand the unique characteristics of smoking behavior change among those living with homelessness.…”
Section: Introductionmentioning
confidence: 99%